A framework for macroscale modelling of inelastic deformations in 3D-woven composites. (September 2021) - Oddy, Carolyn; Ekh, Magnus; Ekermann, Tomas; Hallström, Stefan; Fagerström, Martin
Abstract: The use of 3D-woven composite materials has shown promising results. Along with weight-efficient stiffness and strength, they have demonstrated encouraging out of plane properties, damage tolerance and energy absorption capabilities. The widespread adoption of 3D-woven composites in industry however, requires the development of efficient computational models that can capture the material behaviour. The following work proposes a framework for modelling the mechanical response of 3D-woven composites on the macroscale. This flexible and thermodynamically consistent framework, decomposes the stress and strain tensors into two main parts motivated by the material architecture. The first is governed by the material behaviour along the reinforcement directions while the second is driven by shear behaviours. This division allows for the straightforward addition and modification of various inelastic phenomena observed in 3D-woven composites. In order to demonstrate the applicability of the framework, focus is given to predicting the material response of a 3D glass fibre reinforced epoxy composite. Prominent non-linearities are noted under shear loading and loading along the horizontal weft yarns. The behaviour under tensile loading along the weft yarns is captured using a Norton style viscoelasticity model. The non-linear shear response is introduced using a crystal plasticity inspired approach. Specifically, viscoelasticity is driven on localised slip planes defined by the material architecture. The viscous parameters are calibrated against experimental results and off axis tensile tests are used to validate the model. Highlights: Formulates and presents a macroscale modelling framework for 3D-woven composites. Allows for the introduction of inelastic phenomena in a modular fashion dependent on loading direction. Uses a crystal plasticity inspired model with viscoelastic slip planes to capture experimentally seen non-linear phenomena.